2018
DOI: 10.2174/1871530318666180212102128
|View full text |Cite
|
Sign up to set email alerts
|

Serum DHEA-S, Testosterone and Cortisol Levels in Female Patients with Schizophrenia

Abstract: DHEA-S might be a potential biologic marker for schizophrenia because there is evidence of an association between DHEA-S and the pathophysiology of schizophrenia. However, further research with greater patient numbers is required to verify these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
2
7
2
3
Order By: Relevance
“…Our findings concerning female patients with schizophrenia versus controls differ from those of Bulut et al, who compared 32 pre-menopausal women with stable schizophrenia and 32 age-and sexmatched healthy controls. 39 However, although several investigators report higher levels in female patients versus controls, 40 other researchers obtained contrasting results. 41,42 The most important difference within the context of gender aspects of DHEA-physiology is, of course, the high levels of testosterone in males.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings concerning female patients with schizophrenia versus controls differ from those of Bulut et al, who compared 32 pre-menopausal women with stable schizophrenia and 32 age-and sexmatched healthy controls. 39 However, although several investigators report higher levels in female patients versus controls, 40 other researchers obtained contrasting results. 41,42 The most important difference within the context of gender aspects of DHEA-physiology is, of course, the high levels of testosterone in males.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding women, it was recently reported ( 34 ) that there were statistically significantly higher levels of serum DHEA-S in schizophrenic women than in normal controls. No statistically significant difference was determined between the groups regarding serum testosterone and cortisol levels.…”
Section: Schizophrenia and Estrogenmentioning
confidence: 97%
“…Having analyzed the values in literature, several studies have concluded that female university students have higher levels of value [44,51], while high value orientations of male and female university students vary across the sample group [16,33,[52][53][54][55]. This research has found that female students have higher value levels, which may be due to the socio-cultural and demographic characteristics of the sample.…”
Section: Results Discussion and Recommendationsmentioning
confidence: 96%